Overview of Admixture Mapping. (11th July 2017) - Shriner, Daniel
Abstract: Admixture mapping is a powerful method of gene mapping for diseases or traits that show differential risk by ancestry. Admixture mapping has been applied most often to Americans who trace ancestry to various combinations of Native Americans, Europeans, and West Africans. Recent developments in admixture mapping include improvements in methods and the reference data needed to make inferences about ancestry, as well as extensions of the mapping approach in the framework of linear mixed models. In this unit, the key concepts of admixture mapping are outlined. Several approaches for inferring local ancestry are described, and strategies for performing admixture mapping depending on the study design are provided. Finally, comparisons and contrasts between linkage analysis, association analysis, and admixture mapping are provided, with an emphasis on integrating admixture mapping and association testing. © 2017 by John Wiley & Sons, Inc.